Child Adjustment and Parent Efficacy Scale: Development and Initial Validation of a Parent Report Measure. (August 2014) - Morawska, Alina; Sanders, Matthew R; Haslam, Divna; Filus, Ania; Fletcher, Renee
<x xml:space="preserve">Abstract</x> This study examined the psychometric characteristics of the Child Adjustment and Parent Efficacy Scale (CAPES). The CAPES was designed as a brief outcome measure in the evaluation of both public health and individual or group parenting interventions. The scale consists of a 30‐item intensity scale with two subscales measuring children's behaviour problems and emotional maladjustment and a 20‐item self‐efficacy scale that measures parent's self‐efficacy in managing specific child problem behaviours. A sample of 347 parents of 2–12‐year‐old children participated in the study. Psychometric evaluation of the CAPES revealed that both the intensity and self‐efficacy scales had good internal consistency, as well as satisfactory convergent and discriminant validity. Potential uses of the measure and implications for future validation studies are discussed.